Root-rot of Neem (Azadirachta indica) Caused by Ganoderma applanatum - Chakraborty, R.; Konger, G. (Indian Forester, 1995)
Root rot of neem (Azadirachta indica) is a serious disease caused by Ganoderma applanatum is recorded for the first time from Garo Hills (Meghalaya) even from north-east. Symptoms of the disease, morphology of the pathogen and its identification has been described in this paper.